ANALYSIS OF ESA TEACHING SEQUENCES APPLIED BY THE ENGLISH TEACHERS FOR JUNIOR HIGH SCHOOL STUDENTS: A CASE STUDY - Ayiz, Abdul (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2014)
Up to now the results of teaching and learning process related to the studentsâ engagement and readiness to study as perceived by junior high school students have not been satisfying yet. The studentsâ engagement andÂ readiness are not considered as important elements before going through the lesson.Â Students are mostly considered as empty vessels who are ready to be filled with knowledge by English teachers. As a matter of fact, students need encouraging since at the beginning of the lesson in order toÂ achieve their maximum capacity in learning. Regarding with those important elements, there is an interesting teaching sequence namely E-S-A teaching sequence proposed by Harmer (2007) which can create a very interesting and succesful teaching and learning process. ThisÂ paper therefore discusses the application of E-S-A teaching sequence which includes the studentsâ engagement during the teaching learning process, and the kinds of E-S-A teaching sequences for teaching junior high school students. The engagement indicators indentified five criteria such as body language, consistent focus, verbal participation, studentâs confidence, fun and excitement.Â The data were taken from the two English teachers as the subjects of this study. The two English teachersâ performance towards the application of E-S-A teaching sequence were analyzed and compared. The result of this study presents the studentsâ engagement during the teaching and learning process and various kinds of E-S-A teaching sequence which were employed by English teachers to teach students as appropriate.